Sodium Bisulfite as SO3 Source for Synthesis of Methyl Ester Sulfonate Using RBD Stearin as Raw Material - Mansur, Dieni; Astrini, Nuri; Tasrif (IPTEK The Journal for Technology and Science, 2025)
Methyl Ester Sulfonate (MES) is an anionic surfactant that be used for making cleansing products. MES is a biodegradable product because it is made from vegetable oil. MES can replace LAS (Linear Alkylbenzene Sulfonate) and AS (Alcohol Sulfate) that made from petrochemical substances. Process synthesis of MES was required the source of SO3 which can be obtained from sodium bisulfite. Various of process variables such as temperature and mole ratio between SO3 and methyl ester was required to get the optimal condition of sulfonation process using falling film reactor. In this research was obtained optimal temperature at 900C and mole ratio between sodium bisulfate and methyl ester was 1.6 : 1 giving active matter 32%. The qualities of obtained MES have near to the quality of MES of Chemithon and of LAS. Iod value and color of MES of Chemithon were 0.1–1 and 100 klett respectively while in this research was 6.11 for iod value and 135 klett for the color. Surface tension of LAS was 31.6 dyne/cm while MES as the experimental product rest at 50 dyne/cm.